(untitled) (Research, Society and Development, 2022)
The present work aims to present the relevance of the early diagnosis of endometriosis along with its benefits, as well as to portray the importance of the active role of the nursing team during treatment. The endometrium is one of the tissues of the human body that has different phases and thickness, being located in the innermost part of the uterus. Endometriosis is a chronic and painful inflammatory disease that is present when endometrial cells follow a different flow than expected during menstruation, where instead of being expelled by the uterus at that time, when the condition of endometriosis exists, the cells will migrate. to other places in the pelvis mainly in the fallopian tubes, ovaries or bladder, so there will be an abnormal functioning of the organism. This is a systematic literature review with a qualitative approach, associated with a temporal and epidemiological study of the reported cases of endometriosis examinations and their findings. In order to have an effective professional performance by the team that provides care to the patient, with a focus on the closest nursing, it is essential that these professionals are increasingly trained about the disease, how it affects the women, to map the most successful women and why, so that care management and early diagnosis can be traced.